ANALISIS PENANAMAN SIKAP SOSIAL SISWA MELALUI PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SD NEGERI 029 SUNGAI PINANG - Nadia Adillah Harpizon; Aramudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explain two main aspects: first, the role of teachers in instilling social attitudes among fourth-grade students at SD Negeri 029 Sungai Pinang; second, the factors that facilitate or hinder teachers in this process.The research adopts a qualitative descriptive approach to understand how social attitudes of fourth-grade students at SD Negeri 029 Sungai Pinang are cultivated through Social Studies (IPS) education. Data were gathered through observation, interviews, and documentation. Data analysis utilized the Miles and Huberman model involving data collection, data reduction, data display, and conclusion drawing.The findings indicate that: (1) Teachers employ IPS teaching strategies to instill social values in students, such as modeling positive social interactions both inside and outside the classroom, integrating IPS curriculum with social values, and initiating discussions with positive social messages at the beginning of lessons. Regular evaluations of social attitudes are also conducted. (2) The outcomes of cultivating social attitudes among fourth-grade students at SD Negeri 029 Sungai Pinang through IPS education show successful results categorized as effective. Teachers have effectively instilled values such as honesty, politeness, self-discipline, and tolerance in accordance with predefined indicators